2014
DOI: 10.15197/sabad.1.11.23
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Mediastinal Tumor: Thymolipoma

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Thymolipoma is a rare benign tumor originating in the anterior mediastinum, and comprises 2-9% of all thymic neoplasms (1). Cytogenetic analyses have demonstrated that thymolipoma is a neoplasm of thymic fat (2).…”
Section: Medical Image Of the Month: Thymolipomamentioning
confidence: 99%
See 1 more Smart Citation
“…Thymolipoma is a rare benign tumor originating in the anterior mediastinum, and comprises 2-9% of all thymic neoplasms (1). Cytogenetic analyses have demonstrated that thymolipoma is a neoplasm of thymic fat (2).…”
Section: Medical Image Of the Month: Thymolipomamentioning
confidence: 99%
“…There is no sex or age predilection and affected patients range in age from 3-76 years. Most patients remain asymptomatic until the size of the lesion produced local mass effects, resulting in symptoms such as cough, dyspnea, hemoptysis, chest pain and hoarseness (1,3). Autoimmune diseases, including myasthenia gravis, systemic lupus erythematosus, hypogammaglobulinemia, Graves' disease, and erythroblastopenia, may coexist in 10% patients (1).…”
Section: Medical Image Of the Month: Thymolipomamentioning
confidence: 99%
“…Most frequently located in anterior mediastinum, thymolipoma is diagnosed in patients with ages ranging from two to 67 years, without gender predilection [8,9]. Microscopy shows a tumor mass composed by mature adipose tissue, without atypia, associated with foci of benign thymic tissue, mainly composed of epithelial cells [4,[10][11][12][13].…”
Section:  Introductionmentioning
confidence: 99%
“…[ 1 2 ] The majority of these tumors are clinically quiescent; however, symptomatic patients may present with dyspnea, tachypnea, chest pain, upper respiratory tract infections, and rarely myasthenia gravis. [ 3 4 5 ] Diagnosis should be confirmed radiologically during the preoperative work-up, with pathognomonic features demonstrated on both computed tomography (CT) scan and magnetic resonance imaging (MRI) and with fine-needle aspiration biopsy (FNAB). [ 4 6 7 8 9 ] TLs are benign neoplasms for which complete surgical excision is curative.…”
Section: Introductionmentioning
confidence: 99%